Sistem Pendukung Keputusan Pemberian Kredit Mobil Bekas Menggunakan Metode AHP Pada PT. Batavia Prosperindo Finance Tbk - Permana, Anggit; Siswanto, Siswanto; Alinse, Rizka Tri (Mahesa Research Institute, 2022)
PT. Batavia Prosperindo Finance Tbk is one of the companies engaged in the financing of four-wheeled vehicles. The large number of requests for used car loans requires credit financing companies to make decisions quickly and accurately, previously the process of determining creditworthiness by the company was still using the manual method, so it did not rule out the possibility of miscalculations and errors in reading credit granting data. With these problems, a special application is needed that can assist companies in making decisions using the AHP method to determine creditworthiness quickly and accurately. The AHP (Analytical Hierarchy Process) method is one method to help develop a priority from various options using several criteria (multi criteria). Due to its multi-criteria nature, AHP is quite widely used in setting priorities. With this assessment pattern, the cases found at PT. BPF Bengkulu is very suitable when using this method in solving the problem of providing used car loans. From the results of research conducted by the AHP method, it is able to solve problems in the feasibility of giving used car loans using predetermined criteria and sub-criteria, resulting in a final score with the highest score of 0,458273 and the lowest score of 0,133065 and those eligible for used car loans. there are 3 people and 1 people don't deserve to be accepted..